Clinical and radiographic evaluation of indirect pulp treatment with MTA and calcium hydroxide in primary teeth (in-vivo study) - Vimi George; Suresh Kumar Janardhanan; Balagopal Varma; Parvathy Kumaran; Arun Mamachan Xavier (Wolters Kluwer Medknow Publications, 2015)
Objectives: Clinical and radiographic effects of mineral trioxide aggregate (white MTA) and calcium hydroxide (Dycal) in indirect pulp treatment (IPT) of primary teeth over a period of 6 months. Materials and Methods: A clinical trial with sample size of 40 primary molars between the age group of 5-9 years, of which, 20 teeth were considered, each for MTA and Dycal. Measurements on the digitized radiographs were performed at baseline, third and sixth month, increase in dentin was then measured using Corel Draw software. Result: Independent t-test had indicated that at the end of 3 months and 6 months, a statistically significant increase in dentin thickness with both MTA and Dycal (P-value ≤ 0.001) was found. Within the MTA group, the thickness of dentin formed was 0.089 mm ± 0.031 mm at first 3 months and 0.055 ± 0.022 mm at the second 3 months, (P ≤ 0.001) evaluated using paired t-test. In the Dycal group, increment in dentin deposited was 0.068 mm at the first 3 months and second 3 months, it was 0.030 mm (P-value ≤ 0.001). Conclusion: Clinically and radiographically, MTA is superior to Dycal as a good IPT medicament in primary teeth.